Analisis Pengaruh Pertumbuhan Ekonomi, Tingkat Pengangguran Terbuka dan IPM terhadap Kemiskinan di Provinsi Gorontalo - Syahroni, Syahroni; Anggraini, Eka Dewi (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2025)
This study aims to determine the effect of Economic Growth, Open Unemployment Rate and HDI on poverty rate in Gorontalo Province. This study uses secondary data obtained from the Central Bureau of Statistics (BPS). This study uses time series data for 20 years, from 2004 to 2023. The method used in this research is multiple regression analysis. Based on the results of the study, it is known that the three independent variables simultaneously affect the dependent variable. Partially, the Economic Growth variable has a positive and insignificant effect on the poverty rate in Gorontalo Province. The Open Unemployment Rate variable has a positive and significant effect on the poverty rate. And the HDI variable has a negative and significant effect on the poverty rate in Gorontalo Province. The results of this study are expected to provide a deeper understanding of how variables such as economic growth, unemployment, and HDI can interact in the context of poverty alleviation, especially at the provincial level and can provide policy recommendations to address poverty problems.